2008
DOI: 10.1038/ejcn.2008.45
|View full text |Cite
|
Sign up to set email alerts
|

Effects of conjugated linoleic acid plus n-3 polyunsaturated fatty acids on insulin secretion and estimated insulin sensitivity in men

Abstract: Background/Objectives: Dietary addition of either conjugated linoleic acid (CLA) or n-3 long-chain polyunsaturated fatty acids (n-3 LC-PUFAs) has been shown to alter adiposity and circulating lipids, risk markers of cardiovascular diseases. However, CLA may decrease insulin sensitivity, an effect that may be reversed by n-3 LC-PUFA. Thus, the potential of CLA plus n-3 LC-PUFA to affect insulin secretion and sensitivity in non-diabetic young and old, lean and obese subjects was tested. Subjects/Methods: CLA (3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…However, in our study, we have shown that 7 days of 10E,12Z-CLA treatment does not induce measurable Considerable research has been done examining the delipidating effects of 10E,12Z-CLA, but with confl icting results. While a few human supplementation studies suggest that 10E,12Z-CLA induces insulin resistance ( 17,43 ), many others do not fi nd such a correlation ( 34,(44)(45)(46). Similarly, published in vitro studies present contradicting results, with some suggesting that 10E,12Z-CLA reduces glucose uptake ( 11,47 ) and others suggesting that it enhances it ( 48 ), while some suggest that 10E,12Z-CLA induces lipolysis and/or fatty acid oxidation ( 48 ), and others that it suppresses these responses ( 25,(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, we have shown that 7 days of 10E,12Z-CLA treatment does not induce measurable Considerable research has been done examining the delipidating effects of 10E,12Z-CLA, but with confl icting results. While a few human supplementation studies suggest that 10E,12Z-CLA induces insulin resistance ( 17,43 ), many others do not fi nd such a correlation ( 34,(44)(45)(46). Similarly, published in vitro studies present contradicting results, with some suggesting that 10E,12Z-CLA reduces glucose uptake ( 11,47 ) and others suggesting that it enhances it ( 48 ), while some suggest that 10E,12Z-CLA induces lipolysis and/or fatty acid oxidation ( 48 ), and others that it suppresses these responses ( 25,(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a negative effect on insulin resistance was reported in type 2 diabetic patients; however, this may have been due to the bias in the glucose tolerance between the supplementation and placebo groups and may not have been due to CLA supplementation (144) . A recent study also found increased insulin resistance in older obese subjects, but no effects of combined CLA-n-3 supplementation in lean or obese younger subjects or older lean subjects (153) . Supplementation with the individual isomers, c9,t11-CLA or t10,c12-CLA increased insulin resistance (þ15%) in obese men with the metabolic syndrome (60,78) , whereas a CLA isomer mixture did not affect insulin resistance (60) .…”
Section: Conjugated Linoleic Acid Insulin Resistance and Diabetesmentioning
confidence: 90%
“…clamp (107,153) or the oral glucose tolerance test (50,56,58,65 -67,106,154,155) . Indeed the majority of results on the anti-diabetic properties of CLA relate to studies where only fasting plasma or serum glucose or insulin have been measured, are not the main focus of the study and typically have small sample sizes.…”
Section: Conjugated Linoleic Acid Insulin Resistance and Diabetesmentioning
confidence: 99%
“…Although a series of studies indicates that CLAs attenuate the development of impaired glucose tolerance and hyperinsulinemia (6,10,11), an at least equal number of studies support the notion that CLA intake is associated with serious adverse effects such as impaired insulin sensitivity, and ultimately, insulin resistance (8,12,13). Importantly, the molecular mechanisms underlying the effects of CLAs on glucose homeostasis are not completely understood.…”
mentioning
confidence: 99%